Tragedi Pelanggaran HAM di Masa Orde Baru: Pencarian Keadilan dan Keterbukaan - Fajar Nugroho; Bagus Gymnastiar; Moch Alfi Fahmi Azka; Affan Anshori Ma’ruf; Didi Pramono (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The purpose of this article is to explore the impact of human rights violations during the New Order period in Indonesia on the process of seeking justice. Through a qualitative research approach in the form of literature studies and content analysis, it is used to identify patterns of practices that inhibit openness in the Indonesian legal system. The results of the study highlight the importance of comprehensive legal reform to remedy this dark past, as well as to create a fairer and more transparent legal system for all citizens. The implication of this study is the need for concrete actions to strengthen independent and transparent law enforcement agencies and ensure that past human rights violations are prosecuted fairly. Thus, this article emphasizes the urgency to achieve greater justice in the Indonesian legal system.